Study of Distribution Coefficient of 90Sr on Citumbuk Bentonite and Sukaramai Kaolinite - Setiawan, Budi; Suseno, Heni (EKSPLORIUM, 2017)
The study of distribution coefficient of strontium on bentonite and kaolinite samples, collected from Citumbuk, Bogor and Sukaramai, Padang, has been investigated under batch experiments. The sorption ratio was determined as a function of time, ionic strength and Sr concentration in the solution. The strontium wasextensively absorbed in the samples, with Kd values of 13,700 and 1,600 mL/g for bentonite and kaolinite samples respectively. The other results showed that ionic strength of the solution and initial concentration of Sr have given an effect to 90Sr sorption onto samples.